A longitudinal study of natural antibody development to pneumococcal surface protein A families 1 and 2 in Papua New Guinean Highland children: a cohort study. Issue 1 (December 2016) - Francis, Jacinta; Richmond, Peter; Michael, Audrey; Siba, Peter; Jacoby, Peter; Hales, Belinda; Thomas, Wayne; Lehmann, Deborah; Pomat, William; van den Biggelaar, Anita
Abstract Background Pneumococcal surface protein A (PspA), a conserved virulence factor essential forStreptococcus pneumoniae attachment to upper respiratory tract (URT) epithelia, is a potential vaccine candidate for preventing colonisation. Methods This cohort study was conducted in the Asaro Valley in the Eastern Highlands Province of Papua New Guinea, of which Goroka town is the provincial capital. The children included in the analysis were participants in a neonatal pneumococcal conjugate vaccine trial (ClinicalTrials.gov NCT00219401) that was conducted between 2005 and 2009. We investigated the development of anti-PspA antibodies in the first 18 months of life relative to URT pneumococcal carriage in Papua New Guinean infants who experience one of the earliest and highest colonisation rates in the world. Blood samples and nasopharyngeal swabs were collected from a cohort of 88 children at ages 3, 9, and 18 months to quantify immunoglobulin G (IgG) levels to PspA families 1 and 2 using an enzyme-linked immunosorbent assay and to determine URT carriage. Results Seventy-three per cent (64/88) of infants carriedS. pneumoniae at age 3 months; 85 % (75/88) at 9 months, and 83 % (73/88) at 18 months. PspA-IgG levels declined between ages 3 and 9 months (p < 0.001), then increased between 9 and 18 months (p < 0.001). At age 3 months, pneumococcal carriers showed lower PspA1-IgG levels (geometric mean concentration [GMC] 602 arbitrary units [AU]/ml, 95 % confidence interval [CI] 497–728) than non-carriers (GMC 1058 AU/ml [95 % CI 732–1530];p = 0.008), while at 9 months, PspA1- and PspA2-IgG levels were significantly higher in carriers (PspA1: 186 AU/ml, 95 % CI 136–256; PspA2: 284 AU/ml, 95 % CI 192–421) than in non-carriers (PspA1 87 AU/ml, 95 % CI 45–169; PspA2 74 AU/ml, 95 % CI 34–159) (PspA1:p = 0.037, PspA2:p = 0.003). Conclusion Our findings confirm that PspA is immunogenic and indicate that natural anti-PspA immune responses are acquired through exposure and develop with age. PspA may be a useful candidate in an infant pneumococcal vaccine to prevent early URT colonisation.